Productivity and Nutritive Value of Mutant Benggala Grass (Panicum maximum cv Purple Guinea) in the Saline Soil of Coastal Area in Lebak-Banten Province - Fanindi, A.; Sutedi, E.; Herdiawan, I.; Sajimin; Harmini, H.; Hidayat, C.; Krisnan, R.; Yulistiani, D. (Faculty of Animal Science, Bogor Agricultural University, 2023)
The coastal region of Lebak-Banten is an area with a relatively high population of buffalo. The forage requirement has relied on existing forage with low productivity and quality. The study aimed to investigate the physiological, morphological, and nutritional response of mutant benggala grass in the coastal area and to develop salt-tolerant forage crops with high productivity and nutritive value for livestock. The research was conducted in the Binuangeun coastal area, Muara Village, Wanasalam District, Lebak Regency, located at 6°50’34.4”S and 105°53’23.4”E. This study used a completely randomized block design with a factorial arrangement with 5 replications. The first factor consisted of 4 benggala grass mutants: mutant 12, 18, 36, 56, and a control. The second factor was the location or distance of the planting plots from the coastline (FC), consisting of L1: 50 m FC, L2: 75 m FC, L3: 100 m FC, and L4: 500 m FC, representative of low, moderate, and high salinity levels, and no saline. Observations were made during the dry and rainy seasons. The results showed that mutants 12 and 36 had higher fresh forage production during the rainy season, while mutant 36 had the highest forage production at the L1 location (high salinity conditions) during the dry season. Mutant 12 had higher crude protein values at the L2 location (moderate salinity) than the other mutants and locations (salinity levels) during the dry season. Meanwhile, mutant 18 at the L2 location (moderate salinity) had the highest crude protein value during the rainy season. In addition, mutant 12 had a high proline value at the L1 location (high salinity stress) as a plant adaptation response to salinity stress. The study suggests that mutants 12 and 36 have great potential to be developed into new salt-tolerant forage crop cultivars and can be grown in coastal areas of Lebak-Banten.